2022
DOI: 10.7717/peerj-cs.819
|View full text |Cite
|
Sign up to set email alerts
|

Equity distribution of quality evaluation reports to doctors in health care organizations

Abstract: There are volumes of patient reports generated in any healthcare organization daily. The reports can be very lengthy or of few pages. Maintaining records of patients is essential for ensuring quality medical care. Doctors, apart from their routine activities, are also responsible to sort, examine and archive the generated reports. However, this process consumes doctors’ time, who are already hard-pressed for time. The objective of this study is to search for a method that can assign reports to doctors to ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In our work, several algorithms are proposed to solve the load balancing in the blockchain. On the other hand, several works in literature treated the load balancing or as also known as the fair distribution or the equity distribution [36][37][38][39][40].…”
Section: State Of the Artmentioning
confidence: 99%
“…In our work, several algorithms are proposed to solve the load balancing in the blockchain. On the other hand, several works in literature treated the load balancing or as also known as the fair distribution or the equity distribution [36][37][38][39][40].…”
Section: State Of the Artmentioning
confidence: 99%
“…The novelty of this research is the utilization of the dispatching rules by different modifications; randomized method, clustering approach; probability application algorithm, and multi-start algorithm to schedule quality reports to available physicians. The objective is to guarantee the fair assignment of the number of papers workload [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that overload is an important predictor of burnout [ 22 ]. For this reason, it is important that responsibilities are divided equally among the employees of a clinic to maintain a balance of work demands [ 23 ].…”
Section: Introductionmentioning
confidence: 99%